2008
DOI: 10.2186/jjps.52.167
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow Changes of a Superficial Temporal Artery Before and After Low-level Laser Irradiation Applied to the Temporomandibular Joint Area

Abstract: Low-level laser irradiation applied to the right TMJ area caused an expansion of blood vessels and an increase in blood flow volume. The same result on the contralateral side may be caused by the vasodilator reflex via the hypothalamic thermostat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…These transcription factors in return cause protein synthesis that triggers further effects down‐stream, such as increased cell proliferation and migration, alteration in the levels of cytokines, growth factors and inflammatory mediators, and increased tissue oxygenation . Moreover, NO is known to be a potent vasodilator via its effect on cyclic guanine monophosphate production and it can be speculated that LLLT may cause photodissociation of NO not only from CCO but also from intracellular stores such as nitrosylated forms of both hemoglobin and myoglobin leading to vasodilation and increased blood flow which was reported in several studies . Yamazaki and co‐workers observed an upregulation of hepatocyte growth factor (HGF) and HGF activator expression following irradiation of the backs of Sprague Dawley rats with linear polarized infrared laser .…”
Section: Hair and Types Of Hair Lossmentioning
confidence: 94%
“…These transcription factors in return cause protein synthesis that triggers further effects down‐stream, such as increased cell proliferation and migration, alteration in the levels of cytokines, growth factors and inflammatory mediators, and increased tissue oxygenation . Moreover, NO is known to be a potent vasodilator via its effect on cyclic guanine monophosphate production and it can be speculated that LLLT may cause photodissociation of NO not only from CCO but also from intracellular stores such as nitrosylated forms of both hemoglobin and myoglobin leading to vasodilation and increased blood flow which was reported in several studies . Yamazaki and co‐workers observed an upregulation of hepatocyte growth factor (HGF) and HGF activator expression following irradiation of the backs of Sprague Dawley rats with linear polarized infrared laser .…”
Section: Hair and Types Of Hair Lossmentioning
confidence: 94%
“…The increase in facial temperature on the contralateral side might be caused by the vasodilator reflex via the central nervous system [23]. Although we found no temperature changes during LLLT in this study, an expansion of blood vessels and increase in blood flow could have occurred and influenced the non-treated skin regions during LLLT [22]. A recent within-subject comparison study showed that the combination of LLLT with a hair growth promoter had a greater effect on hair regrowth than did either independently [24].…”
Section: Discussionmentioning
confidence: 50%
“…Makihara et al demonstrated that the increase in facial temperature and blood temperature in the stimulated region by continuous laser irradiation caused an expansion of blood vessels and an increase in blood flow volume. Moreover, this process can also cause an increase in facial temperature in unstimulated regions [22]. The increase in facial temperature on the contralateral side might be caused by the vasodilator reflex via the central nervous system [23].…”
Section: Discussionmentioning
confidence: 99%
“…Raggi used a 630 nm wavelength to irradiate athletes’ legs intravenously [15]. Mahikara irradiated the superficial temporal artery with CO 2 laser [8]. He concluded that 10 minutes after stopping irradiation, the diameter and blood flow volume of the artery had increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation of the treated region is reported to cause the expansion of blood vessels and an increased blood flow volume. The increase in blood flow is probably caused by the vasodilator reflex via the central nervous system [8]. …”
Section: Introductionmentioning
confidence: 99%